2021
DOI: 10.1016/j.jcmgh.2020.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Roles of CCR2 and CCR5 for Hepatic Macrophage Polarization in Mice With Liver Parenchymal Cell-Specific NEMO Deletion

Abstract: Macrophages critically regulate liver inflammation. Using a genetically determined hepatitis mouse model we found that CCR2 controls monocyte and macrophage recruitment to injured livers, while CCR5-dependent functions of liver macrophages limit hepatic injury, thereby reducing steatosis and hepatocarcinogenesis. BACKGROUND & AIMS: Macrophages are key regulators of inflammation and cancer promotion in the liver, and their recruitment and activation is linked to chemokine receptor signaling. However, the exact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Recently, it was demonstrated that both CCR2 and CCR5 deficiency/inhibition led to reduced fibrosis, and sole CCR5 deficiency increased steatosis and the incidence of HCC in the model of NEMO LPC-KO mice. While CCR2 controlled the recruitment of monocytes to injured livers, CCR5+ macrophages limited liver injury in NEMOLPC-KO mice (CCR5-dependent differential function), thereby reducing steatosis and hepatocarcinogenesis [ 131 ]. In the hypoxic environment of HCC, HIF-1a enhanced the expression of triggering receptor expressed on myeloid cells-1 (TREM-1) in TAMs, leading to immunosuppression through the impairment of the cytotoxic functions of CD8+ T cells.…”
Section: Critical Analysis Of Data and Future Perspectivesmentioning
confidence: 99%
“…Recently, it was demonstrated that both CCR2 and CCR5 deficiency/inhibition led to reduced fibrosis, and sole CCR5 deficiency increased steatosis and the incidence of HCC in the model of NEMO LPC-KO mice. While CCR2 controlled the recruitment of monocytes to injured livers, CCR5+ macrophages limited liver injury in NEMOLPC-KO mice (CCR5-dependent differential function), thereby reducing steatosis and hepatocarcinogenesis [ 131 ]. In the hypoxic environment of HCC, HIF-1a enhanced the expression of triggering receptor expressed on myeloid cells-1 (TREM-1) in TAMs, leading to immunosuppression through the impairment of the cytotoxic functions of CD8+ T cells.…”
Section: Critical Analysis Of Data and Future Perspectivesmentioning
confidence: 99%
“…In the model of LPS-induced endotoxemia, the technique of macrophage depletion and reconstitution has been used to investigate the role of macrophages ( Fu et al, 2020 ). Recent studies demonstrated that in vivo tracking of transplanted macrophages reveals specific homing in the liver ( Bartneck et al, 2021 ; Nishiwaki et al, 2020 ), while little is known about the location where transplanted macrophages produce IL-12 and mediate IFN-γ production during sepsis. We depleted phagocytes with clodronate liposome and found when macrophage-depleted mice received BMDM isolated from same genotype, serum IL-12 and IFN-γ bounced back to the levels where endogenous macrophages have not yet been depleted ( Figure 8C ).…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] Cytokine release leads to a secondary recruitment and activation of neutrophils and predominant polarization of macrophages to the M1 proinflammatory phenotype. 22,23 It is therefore likely that hepatic tissue injury, which also involves oxidative stress and mitochondrial dysfunction, 4,5 results from both an immune cell mediated effect and a direct toxin-hepatocyte interaction. It is also well known that immune cell infiltration in any disease can have ambivalent consequences as proregenerative subsets, such as the M2 macrophage phenotype might propel the regenerative response.…”
Section: The Rational Of Using G-csf To Treat End-stage Liver Diseasementioning
confidence: 99%